The effect of health visitors on breastfeeding in Glasgow - Broadfoot Mary; Britten Jane; Tappin David; McInnes Rhona (BMC, 2006)
Abstract Background The UNICEF Baby Friendly Initiative includes a community component to help women who want to breastfeed. This study aimed to document the health visitor role in promoting and supporting breastfeeding in Glasgow during 2000 and the effect it had on breastfeeding rates. Methods Glasgow, UK, has a population of 906,000, with approximately 10,000 births per year. Glasgow has high levels of material deprivation and traditionally low breastfeeding rates. This was a cross-sectional study in January 2000 which used a postal questionnaire to document individual health visitors' interventions, activities and attitude towards breastfeeding. Infant's breastfeeding data collected routinely by the Child Health Surveillance programme from 1 August 1998 to 28 February 1999 was directly matched with interventions, activities and attitudes reported by their own health visitor. Results 146/216 (68%) health visitors completed and returned the questionnaire. 5401 child health records were eligible and 3,294 (58.2%) could be matched with health visitors who returned questionnaires. 2145 infants had the first visit from 8 to 20 days of age and the second 3 to 7 weeks later. At the first postnatal visit 835 of 2145 (39%) infants were breastfed (median age of 13 days) and 646 (30%) continued to breastfeed at the second visit (median age 35 days). Infants being breastfed at the first visit were significantly more likely to be fed infant formula at the second visit if their health visitors had had no breastfeeding training in the previous two years (OR1.74 95%CI 1.13, 2.68). Conclusion It is essential that Health Visitors are specially trained to support breastfeeding postnatally.